PEMANFAATAN UMBI-UMBIAN SEBAGAI BAHAN BAKU UNTUK PEMBUATAN PRODUK SISTIK UBI UNGU DI PASIR KIDUL PURWOKERTO BARAT - Eti Wahyuningsih; Gita Anggraeni; Dheni Atmiasih (Jurnal Abdi Masyarakat Multidisiplin, 2023)
One of the villages in Banyumas District, Central Java Province, Indonesia, which utilizes part of its land for yards, dryland and wetland agriculture, plantations and tropical forests is Pasir Kidul Village. There are various tubers in Pasir Kidul including purple sweet potatoes. Some of the purple sweet potatoes in Pasir Kidul Village are only sold at a very cheap price of Rp. 2500,-/kg. So far, the people of Pasir Kidul Village have used purple sweet potatoes in their raw form (unprocessed), even during the main harvest some unsold purple sweet potatoes are distributed to the surrounding community free of charge. This happens because of limited information and knowledge in product development that can be produced from purple sweet potato raw materials, the community also does not understand the simple technology that can be applied to the purple sweet potato they have. The solution offered in this PKM is processing purple sweet potatoes into purple sweet potato cysts with the aim of increasing income, business independence, and reducing unemployment for the people of Pasir Kidul Village. The purple sweet potato cystic product is used as a solution to overcome partner problems for several reasons, namely: 1) both products have wider market potential, 2) higher selling prices, 3) consumers are not limited by age (from children to the elderly ), 4) has a very high nutritional value, 5) good for health. The proposed activity plan for PKM this is market research on the selling price of purple sweet potato cysts, making production designs, training on making purple sweet potato product processing into purple sweet potato cysts, program evaluation, and mentoring. The results of the PKM went smoothly, the openness of the management of the Subsidiaries of the Fatayat NU Purwokerto Barat Branch in conveying problems and discussions related to solutions to problems was obtained well. Currently, the management of the Sub-Branch Office of Fatayat NU, Purwokerto Barat, know how to collaborate with other parties to market and improve online marketing so that the purple sweet potato cysts are better known and there are many buyers.